Case Report: Etoposide-nedaplatin induced rhabdomyolysis in a small cell lung cancer patient - Xu, Xiaohu; Wu, Xiao; Zhang, Mingmin; Wang, Qi (Frontiers in Pharmacology, 2023)
Rhabdomyolysis syndrome refers to the breakdown and necrosis of muscle tissue due to various reasons and caused by the release of intracellular contents into the blood stream, which can lead to acute renal failure or even death. In this article, we describe for the first time a case report of severe rhabdomyolysis induced by etoposide-nedaplatin chemotherapy in a small cell lung cancer (SCLC IIIb) patient. The patient developed progressive general muscle pain and weakness after the first cycle of chemotherapy, accompanied by elevated creatine kinase (CK), myoglobin (Mb), alanine aminotransferase (ALT), spartate aminotransferase (AST), and lactate dehydrogenase (LDH). Examination of and inquiry regarding the medical history were used to exclude various factors of rhabdomyolysis caused by trauma, strenuous activities, infections, drugs, hyperthermia, and immunity; the patient was diagnosed with severe rhabdomyolysis induced by chemotherapy. After treatment with intravenous fluids and methylprednisolone, the patient’s symptoms were relieved and laboratory results were significantly improved. An unexpected situation arose, in that the lung CT scan showed that the lung mass was significantly smaller than that before chemotherapy; the reason for this is not clear. Rhabdomyolysis induced by anti-cancer drugs, especially chemotherapy drugs, is rarely reported and easily overlooked. Therefore, physicians should be aware of this rare but potentially serious complication when using chemotherapy drugs.